Analisis Kinerja Keuangan Atas Pelaksanaan Otonomi Daerah Kabupaten Toraja Utara Sebelum dan Setelah Pandemi COVID-19 - Grace Randa Kadang; Muspa Muspa; Novita Rosanti; Dhita Pratiwi Ar (Movere Journal, 2025)
This research aims to determine the comparison of financial performanceregarding the implementation of regional autonomy in North Toraja Regency before andafter the Covid-19 pandemic. This research was conducted in (BPKAD) North Toraja witha research period of 6 months. This research uses a comparative quantitative method byanalyzing using ratios, namely the degree of decentralization ratio, independence ratio,efficiency ratio, effectiveness ratio and financial dependence ratio and each ratio has ameasurement scale. The research results show less than optimal performance in theimplementation of regional autonomy in the pre- and post-Covid era, which is reviewedfrom five aspects of regional finance, namely the degree of decentralization ratio,independence ratio, efficiency ratio, effectiveness ratio and financial dependency ratio